The Torsion of a Nonhomogeneous Visco-Elastic Bar of Elliptic Cross-Section - El Karamany, A.S.; Kodsy, F.E. (Engineering Transactions, 1988)
An exact solution for a torsion problem of a nonhomogeneous visco-elastic bar of elliptic cross-section is presented. A method based on elastic-viscoelastic analogy is used to obtain the stress distribution in the cross-section of the bar. The numerical results show that the nonhomogeneity reduces the stress as compared to the homogeneous one.